The Role of β2-Adrenergic Receptors in Inflammation and Allergy - Sitkauskiene, Brigita; Sakalauskas, Raimundas (Current Drug Targets - Inflammation & Allergy, 2005)
Essential role of β2-adrenoreceptor (β2AR) in airway relaxation is well established. Nevertheless, β2AR seems playing an actual role in allergy and inflammation. Interaction between β2AR and proinflamatory cytokines in airway smooth muscle has been revealed. Being located on proinflamatory cells, β2ARs may influence function of these cells in vivo. It was clear established, that stimulation of β2AR inhibits release of proinflamatory mediators from mast cells, influences T-cell growth and function, eosinophil survival and function, including GM-CSF- or PAF-induced degranulation. Stimulation of β2ARs, located on alveolar macrophages and epithelial cells, has ambiguity influence on their regulation and function, including phagocytosis and mediator secretion, in vivo. Vascular responses, resulting in inhibition of plasma exudation were confirmed, but modulation of sensory nerves via β2AR is not certain yet. β2AR-agonists are effective in treatment of immediate allergic reactions, but desensitisation of β2ARs on inflammatory cells may result in paradoxical effects, especially in asthma. In summary, it is clear that ?2ARs may play an anti-inflammatory role in vitro. Unfortunately, in vitro data have shown limited applicability in vivo; therefore further research in this field is required.
Keywords: adrenergic receptor